(untitled) (Proceedings of the International Conference on Education, 2021)
: The transition of teaching Mathematics from English language to Mother tongue-based in primary grades has brought challenges and problems to teachers concerned. This paper attempts to determine those problems encountered by these teachers teaching Mathematics using Mother Tongue and the possible recourses they employed to address those problems. The study employed the descriptive- survey method of research using a questionnaire, purposively distributed to seven principals and thirty-three teachers who are identified respondents. Weighted mean and ranking system were utilized as measures to find out the prevalent problem, its recourses and how frequent they used the recourses. Based on the data gathered and analyzed, it was found out that language is the most prevalent problem in teaching Mathematics using mother tongue of which, insufficient translation from English term to mother tongue ranks on top. Whereas, in the area of instruction, content delivery using MT as medium for instruction is the major problem, while for teaching materials, the incomplete or delayed arrival of instructional material prevailed the most. The result further revealed that the identified problems in terms of language, teaching instruction and teaching material are mostly described as serious problem. To address the problem with regards to language; the teachers used other MT terms that fits the unfamiliar MT term, allowing pupils to use their own preferred term and remain to use English translation/ term. While for instruction; teachers use translation, drills, code switching, and pictures, whereas for teaching materials, teachers used school funds for material production, utilize local magazines as supplement, share resources to other grade level and borrow materials from other schools. All these recourses were all oftentimes applied/used. From the results, it is recommended that becoming teachers should be equipped with knowledge on teaching MTB-MLE and newly-hired teachers should attend seminars and trainings regarding such implementation. Principals or school heads should find measures for speedy delivery of learning materials